The Education Effect of AADE7TM Model on Self-Care Activities in Type 2 Diabetes Mellitus Patients - Zulkibli Zulkibli; Dedi Damhudi; Susito Susito (Media Karya Kesehatan, 2023)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by high blood glucose levels due to a lack or ineffective use of the hormone insulin. If not treated properly, it will result in complications, even amputation and death. However, many patients still do not understand their disease, lack motivation, and have poor self-care activities. Therefore, it is important to provide education on the AADE7TM model, namely 7 tips for self-care habits, which have become a trademark of AADE, an organization consisting of multidisciplinary health professionals who are experts in diabetes education and diabetes self-care management. An organization comprises multidisciplinary health professionals who are experts in diabetes education and diabetes self-care management. The Seven tips include (1) eating healthy, (2) being active, (3) monitoring, (4) taking medication, (5) problem solving, (6) healthy coping, and (7) reducing risks so that there will be increased self-care activities.  Objective to determine the effect of AADE7TM model education on self-care activities in type 2 diabetes mellitus patients. Research methods: Quantitative research type with quasi-experiment method, nonrandomized control group pre-test and post-test design. With purposive sampling on 30 patients, 15 patients in the experimental group and 15 in the control group. The experimental group was given AADE7TM model education, and the control group received conventional education. Data analysis techniques t-test. There was a difference in mean self-care in the experimental group in the pre-test, with a score of 19,800, and in the post-test, 33,066, with a p-value of 0.001.There was no difference in mean self-care in the control group at the initial and final measurements, with a p-value of 0.060. There was a difference in self-care activities after the AADE7TM model education in the experimental group compared to the final measurement in the control group, with a p-value of 0.001.Conclusion: there was an influence of AADE7TM model education on self-care activities in type 2 diabetes mellitus patients. Keywords: AADE7TM, self-care activities, diabetes mellitus.